Contexts of political protest in Western democracies: Political organization and modernity - Edeltraud Roller; Bernhard Weßels (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1996)
This paper provides a comparative analysis of two contextual determinants of protest participation in 17 Western democracies at the beginning of the 1990's. The two determinants are the individual's organizational context and the national context of political and socioeconomic conditions. The organizational context is defined as the close context of political protest arising due to social interaction, while the national context is defined as the wide context, constituting of extra-individual factors. The relationship between the close context and political protest is specified by theories of mobilization, whereas in the case of the wide context modernization theories are used. Individual-level analysis of the effects of the close context reveals that protest participation increases with an individual's embeddedness in political organizations. This holds true not only for memberships in new but also in traditional political organizations. However, the organizational context does not contribute equally to all forms of protest. Its impact is stronger on legal than on illegal forms of protest. Concerning the wide context of political protest, evidence is provided by aggregate-level analysis that variations in the extent of legal protest between countries can be explained by different levels of political and socioeconomic modernity of societies. The more modern a society, the higher the extent of legal protest participation and the less legal protesters articulate demands for radical change to the societal order. To the contrary, the extent of illegal protest participation cannot be explained by a modernization approach. The research on the close and wide context of political protest indicates that the enlargement of the action repertory of citizens to include legal protest, is part of the modernization of politics. – – Für 17 westliche Demokratien wird für Anfang der 90er Jahre im internationalen Vergleich der Einfluß von zwei Kontextfaktoren auf die Beteiligung an politischem Protest untersucht. Zum einen ist dies der organisatorische Kontext von Individuen, der als enger Kontext definiert wird, weil er auf sozialen Interaktionen basiert Zum anderen ist dies der nationale politische und sozioökonomische Kontext, der hier als weiter Kontext definiert wird, da er sich auf extraindividuelle Faktoren bezieht Der Zusammenhang zwischen engem Kontext und politischem Protest wird durch Mobilisierungstheorien spezifiziert, der Einfluß des weiten Kontextes mithilfe von Modernisierungstheorien. Die Individualdatenanalyse der Effekte des engen Kontextes zeigt, daß die Beteiligung an politischem Protest mit dem Ausmaß der individuellen Einbettung in politische Organisationen zunimmt Dieser Zusammenhang gilt nicht nur für die Mitgliedschaft in neuen, sondern auch in traditionellen politischen Organisationen. Der organisatorische Kontext trägt hingegen nicht in gleicher Weise zu legalen und illegalen Protestaktivitäten bei. Er fördert in stärkerem Maße die Beteiligung an legalen Protestformen. Die Aggregatdatenanalyse der Effekte des weiten Kontextes zeigt, daß Unterschiede im Ausmaß der individuellen Beteiligung an legalen Protestformen zwischen Ländern durch deren unterschiedliches politisches und sozioökonomisches Modernitätsniveau erklärt werden kann. Je moderner eine Gesellschaft ist, desto höher ist das Ausmaß legaler Protestbeteiligung und um so weniger werden Forderungen nach einer radikalen Veränderung der Gesellschaft von den Bürgern artikuliert, die legale Protestformen einsetzen. Im Gegensatz zu legalen Formen kann das Ausmaß der Beteiligung an illegalen Formen des Protests nicht mithilfe von Modernisierungsansätzen erklärt werden. Insgesamt weisen die Ergebnisse daraufhin, daß die Ausweitung des Aktionsrepertoires der Bürger um den legalen Protest Teil der Modernisierung des Politischen ist.
Keywords: 300